Insulin resistance in offspring of hypertensive parents. Issue 6896 (10th July 1993) - Beatty, O L; Harper, R; Sheridan, B; Atkinson, A B; Bell, P M
Abstract : OBJECTIVE--To determine if insulin resistance is present in normotensive adults at increased risk of developing hypertension. DESIGN--Normotensive subjects with at least one hypertensive parent were paired with offspring of normotensive parents (controls), being matched for age, sex, social class, and physical activity. SETTING--Outpatient clinic. SUBJECTS--30 paired subjects (16 men and 14 women) with and without a family history of hypertension, aged 18-32, with a body mass index < 25 kg/m2, with blood pressure < 130/85 mm Hg, and not taking drugs. INTERVENTIONS--Euglycaemic glucose clamp (two hour infusion of insulin 1 mU/kg/min) and intravenous glucose tolerance test (injection of 100 ml 20% glucose). MAIN OUTCOME MEASURES--Insulin mediated glucose disposal and insulin secretion. RESULTS--The offspring of hypertensive parents had slightly higher blood pressure than did the controls (mean 117 (SD 6) v 108 (5) mm Hg systolic, p = 0.013; 76 (7) v 67 (6) mm Hg diastolic, p = 0.017). Their insulin mediated glucose disposal was lower than that of controls (29.5 (6.5) v 40.1 (8.6) mumol/kg/min, p = 0.002), but, after adjustment for blood pressure, the difference was not significant (difference 6.9 (95% confidence interval -1.5 to 15.3), p = 0.10). Insulin secretion in the first hour after injection of glucose was slightly but not significantly higher in the offspring of hypertensive patients (9320 (5484) v 6723 (3751) pmol.min/l). The two groups had similar concentrations of plasma glucose (5.2 (0.3) v 5.1 (0.4) mmol/l), serum cholesterol (4.4 (0.8) v 4.6 (0.8) mmol/l), serum triglyceride (0.89 (0.52) v 0.68 (0.27) mmol/l), and serum low density lipoprotein cholesterol (2.81 (0.65) v 2.79 (0.61) mmol/l). The offspring of hypertensive parents, however, had lower serum concentrations of high density lipoprotein cholesterol (1.24 (0.31) v 1.56 (0.35) mmol/l, p = 0.002) and higher serum concentrations of non-esterified fatty acids (0.7 (0.4) v 0.4 (0.4) mmol/l, p = 0.039). CONCLUSIONS--Young normotensive subjects who are at increased risk of developing hypertension are insulin resistant.